Management by Values - a strategic dimension = Management by Values - wymiar strategiczny - Krzakiewicz, Kazimierz (Zielona Góra: Faculty of Economics and Management Press)
This article presents the strategic aspects of the Management by Values concept. The author tries to prove that implementation of this concept in an organization helps to form a stable and competitive organizational culture, which is accepted by the organization's members. MBV can be defined as a philosophy and practice of management, linking the basic values of the organization with its strategic objectives. It has been assumed that leadership has always been connected with human values.
Keywords: wartości pragmatyczne; wartości etyczno-społeczne; wartości emocjonalne; strategia organizacji; zarządzanie przez wartość; pragmatic values; ethical values; social values; emotional values; organization's strategy; Management by Values